COMPARISON EFFICACY OF ITS AND 18S rDNA PRIMERS FOR DETECTION OF FUNGAL DIVERSITY IN COMPOST MATERIAL BY PCR-DGGE TECHNIQUE - Tu Anh, Pham Ngoc; Thu Hang, Pham Thi; Quynh Tram, Le Thi; Minh, Nguyen Thanh; Dang Khoa, Dinh Hoang (Vietnam Journal of Biotechnology, 2018)
Through composting process, biosolid wastes are gradually transformed into compost material which can be used as soil fertilizer. Among microorganisms involved in composting process, fungi play important roles because they break down complex substrates, such as ligno-cellulose. Recently, PCR-DGGE technique has been considered as a useful tool for analysis of fungal diversity in environmental samples. Among other factors, primer set selection is necessary for successful of the PCR-DGGE analysis. There are several PCR primer sets targeting fungal variable regions of 18S ribosomal DNA (rDNA) and internal transcribed spacer (ITS) for the use in community analyses, however there exist just few reports on efficacy of these primers in studying fungal communities in compost materials. In this study, four different primer sets were tested, including EF4/Fung5 (followed by EF4/NS2-GC), EF4/ITS4 (followed by ITS1F-GC/ITS2), NS1/GC-Fung, and FF390/FR1-GC. Extracted DNA from compost materials often contains co-extracted humic substances and other PCR inhibitors. Therefore, the primers were tested for (i) tolerance to the PCR inhibitors presenting in the DNA extracted from compost materials, and (ii) efficacy and specificity of the PCR. The results showed that of the four primer sets, only FF390/FR1-GC achieved both criteria tested whereas the other three did not, i.e. primer EF4/ITS4 had low tolerance to PCR inhibitors, primers EF4/Fung5 was low in PCR amplification efficacy, whereas primers EF4/ITS4 created unspecific products. DGGE analyses of PCR products amplified with the primer set FF390/FR1-GC showed single bands for reference pure cultures Penicillium sp., Aspergillus sp., and Trichoderma sp., as well as distinctly separated bands for the fungal communities of three different composting materials. Thus, the primer set FF390/FR1-GC could be suitable for studying structure and dynamic of fungal communities in compost materials.